Gender Stereotypes and Homophily in Team Formation - Antonio Cabrales; Lorenzo Ductor; Ericka Rascón-Ramírez; Ismael Rodriguez-Lara (CESifo GmbH, 2025)
Women often find themselves in teams that hinder their productivity and earnings. We analyze the role of homophily and gender stereotypes in preferences for team formation and examine the effect of information on changing these preferences. We find that women are expected to perform better in female-type tasks (such as text and emotion-recognition). However, people prefer forming teams with their same gender. Our findings suggest that information can mitigate -but it does not eliminate- the influence of homophily on team formation.
Keywords: C91; D03; D60; D81; 330; gender differences; expectations; collaboration; network formation; team production